The Glen Grey Act and its effects upon the native system of land tenure in Cape Colony and the Transkeian Districts - Wiggins, Ella (Department of Historical Studies, 2019)
The first object of this essay is to trace any tendency of the Natives in the Cape Colony to modify their own communal system of land occupation in favour of any system more approximating to the Western ideal of individual tenure or ownership. The significance of any such tendency need not be emphasised. The communal occupation of land is one of the most essential bases of tribal organisation. It is closely linked up with the organisation of the family as an economic unit, as well as with the tribe in that aspect. It is, indeed, at the very roots of the Native family and tribal system. To trace any changes from communal to individual occupation mu.st be a part, therefore, of a larger study, viz., of the development of tribal life so as to admit of free economic action by individuals untrammelled by the bonds of tribal custom.